Fluid generation and evolution during exhumation of deeply subducted UHP continental crust: Petrogenesis of composite granite-quartz veins in the Sulu belt, China - Wang, S.; Wang, L.; Brown, M.; Piccoli, P.; Johnson, Tim; Feng, P.; Deng, H.; Kitajima, K.; Huang, Y. (Wiley - Blackwell, 2017)
Composite granite-quartz veins occur in retrogressed ultrahigh pressure (UHP) eclogite enclosed in gneiss at General's Hill in the central Sulu belt, eastern China. The granite in the veins has a high-pressure (HP) mineral assemblage of dominantly quartz+phengite+allanite/epidote+garnet that yields pressures of 2.5-2.1 GPa (Si-in-phengite barometry) and temperatures of 850-780°C (Ti-in-zircon thermometry) at 2.5 GPa (~20°C lower at 2.1 GPa). Zircon overgrowths on inherited cores and new grains of zircon from both components of the composite veins crystallized at c. 221 Ma. This age overlaps the timing of HP retrograde recrystallization dated at 225-215 Ma from multiple localities in the Sulu belt, consistent with the HP conditions retrieved from the granite. The eHf(t) values of new zircon from both components of the composite veins and the Sr-Nd isotope compositions of the granite consistently lie between values for gneiss and eclogite, whereas d18O values of new zircon are similar in the veins and the crustal rocks. These data are consistent with zircon growth from a blended fluid generated internally within the gneiss and the eclogite, without any ingress of fluid from an external source. However, at the peak metamorphic pressure, which could have reached 7 GPa, the rocks were likely fluid absent. During initial exhumation under UHP conditions, exsolution of H2O from nominally anhydrous minerals generated a grain boundary supercritical fluid in both gneiss and eclogite. As exhumation progressed, the volume of fluid increased allowing it to migrate by diffusing porous flow from grain boundaries into channels and drain from the dominant gneiss through the subordinate eclogite. This produced a blended fluid intermediate in its isotope composition between the two end-members, as recorded by the composite veins. During exhumation from UHP (coesite) eclogite to HP (quartz) eclogite facies conditions, the supercritical fluid evolved by dissolution of the silicate mineral matrix, becoming increasingly solute-rich, more 'granitic' and more viscous until it became trapped. As crystallization began by diffusive loss of H2O to the host eclogite concomitant with ongoing exhumation of the crust, the trapped supercritical fluid intersected the solvus for the granite-H2O system, allowing phase separation and formation of the composite granite-quartz veins. Subsequently, during the transition from HP eclogite to amphibolite facies conditions, minor phengite breakdown melting is recorded in both the granite and the gneiss by K-feldspar+plagioclase+biotite aggregates located around phengite and by K-feldspar veinlets along grain boundaries. Phase equilibria modelling of the granite indicates that this late-stage melting records P-T conditions towards the end of the exhumation, with the subsolidus assemblage yielding 0.7-1.1 GPa at <670°C. Thus, the composite granite-quartz veins represent a rare example of a natural system recording how the fluid phase evolved during exhumation of continental crust. The successive availability of different fluid phases attending retrograde metamorphism from UHP eclogite to amphibolite facies conditions will affect the transport of trace elements through the continental crust and the role of these fluids as metasomatic agents interacting with the mantle wedge in the subduction channel.